Empowerment of KTT Wana Sari Mekar in green economy-based product entrepreneurship through organic fertilizer - Gunawan, Ketut; Wiryanata, I Wayan Gede; Sutama, Gede Rai; Gunawan, Kadek Dwi Hendratma (Research and Social Study Institute, 2024)
This community service program aimed to empower the Wana Sari Mekar farmer group in entrepreneurship based on the green economy through organic fertilizer production. The Participatory Rural Appraisal (PRA) method was employed, involving stages of preparation, awareness, training, technology implementation, mentoring, and evaluation. The program successfully empowered the Wana Sari Mekar group to produce and market organic fertilizer as a featured product in Galungan village. The first cycle focused on the production of liquid and solid organic fertilizers. Appropriate technology transfer, including a chopping machine and fermentation containers, addressed waste management issues faced by the group and provided a new source of income while reducing chemical fertilizer use. The human resource quality improved as the group members gained skills in managing businesses related to organic products. The fertilizers produced met quality standards after testing, ensuring their effectiveness. The program's sustainability continues in the second cycle with the production of biopesticides, expanding market reach, and increasing sales turnover for Wana Sari Mekar.